Phosphate adhesive and preparation method thereof
By using low-price and mixed valence metal oxides as curing promoters, the polymerization reaction of phosphate-copper oxide adhesive is solved, and the problem of slow curing speed of phosphate-copper oxide adhesive at room temperature is achieved, and the low-temperature conditions are achieved The effect of rapid curing and high strength is reduced, and the amount of curing accelerator is used.
Patent Information
- Application Number
- CN202411408011.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-14
AI Technical Summary
The existing phosphate-copper oxide adhesives cure at room temperature slowly and are difficult to achieve high strength in a short period of time. The added curing accelerators such as calcium oxide or magnesium oxide will cause excessive reaction and overheating, affecting the application operation.
Low-valent metal oxides and/or mixed valent metal oxides are used as curing accelerators to promote the polymerization of phosphoric acid and copper oxide/iron oxide through the affinity of their spacing to positive and negative electrical centers, thereby increasing the curing speed and Reduce the initial temperature of the reaction.
During the same applicable period, phosphate adhesives can quickly cure at room temperature to achieve higher strength, and use less curing accelerator, which solves the contradiction between glue application time and curing strength, and the process is simple and efficient.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic adhesive production, and in particular relates to a phosphate adhesive and a preparation method thereof. Background Art
[0002] Phosphate-copper oxide adhesive plays an important role in the repair, production and bonding of metal, glass, ceramics and other materials due to its excellent bonding performance, especially its applicability in the temperature range of -183℃~2900℃. It has high bonding strength, small curing shrinkage, excellent durability, low price, no pollution, simple preparation process, short production cycle and easy use. It is a widely used and promising adhesive.
[0003] The phosphate-copper oxide adhesive system has a slow curing speed at room temperature, and usually needs to be externally heated or added with highly alkaline metal oxides, such as calcium oxide and magnesium oxide, to promote the cross-linking and curing of the adhesive system. However, this technology has the following problems: First, the curing speed of the phosphate-copper oxide adhesive system is greatly affected by temperature. When long-term gluing is required, the adhesive cannot be quickly cured at room temperature, affecting the construction progress; in order to promote the reaction, different masses of calcium oxide and magnesium oxide can be added to the mixed adhesive. If the amount added is small, the system has a long applicability period, which can provide enough time to evenly apply the adhesive to the part to be bonded. However, when the adhesive is taken out of the container and evenly dispersed, the curing speed will drop significantly due to the accelerated heat dissipation rate, resulting in the adhesive being unable to reach the required strength in a short time. If the curing speed of the adhesive is to be accelerated to obtain a higher curing strength, more calcium oxide or magnesium oxide needs to be added to promote a rapid reaction. However, this rapid reaction is accompanied by a large amount of heat release, that is, the initial reaction temperature is high, which leads to an excessively fast curing rate of the adhesive, causing the adhesive to lose its applicable period and making it difficult to complete the sizing operation within the specified time. Chinese Patent Publication No. CN101307212A provides an inorganic adhesive, which uses one or more of aluminum oxide, zirconium oxide, and silicon oxide as an inorganic curing agent, and a combination of one or more of nano-carbon powder, Al-Si alloy powder, Ni powder, boron powder, silicon powder, carbon fiber, quartz fiber, and aluminum silicate fiber as a toughening and reinforcing agent to prepare a high-temperature resistant inorganic adhesive; Chinese Patent Publication No. CN101358111A provides an adhesive and a preparation method thereof, which uses a mixture of aluminum oxide powder, zirconium oxide powder and zinc oxide powder or aluminum nitride powder as a curing agent to prepare an adhesive. In summary, the prior art has not yet solved the contradiction between sufficient sizing time and higher curing strength.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a phosphate adhesive and a preparation method thereof. The phosphate adhesive is prepared by using low-valent metal oxides and / or mixed-valent metal oxides as curing accelerators. Compared with the adhesives in the prior art, the phosphate adhesive can be quickly cured at room temperature to achieve higher strength under the same application period and uses less curing accelerator.
[0006] In order to solve the above technical problems, the technical solution of the present invention is as follows:
[0007] The first object of the present invention is to provide a phosphate adhesive, wherein the raw materials of the phosphate adhesive include phosphate-based glue, copper oxide / iron oxide, and a curing accelerator, and the curing accelerator is a low-valent metal oxide and / or a mixed-valent metal oxide.
[0008] Low-valent metal oxides and / or mixed-valent metal oxides can be oxidized (easily lose electrons or have affinity for positive charge centers) or reduced (easily gain electrons or have affinity for negative charge centers) because of their intermediate valence states. The polymerization reaction of phosphoric acid and copper oxide / iron oxide is essentially the polymerization of positive and negative charge centers, and the key to accelerating the reaction process is free H + The low-valent metal oxides and / or mixed-valent metal oxides are favorable for the movement of H due to their affinity for positive and negative electron centers. + The supply and adsorption of H + The free transfer of phosphoric acid and copper oxide / ferric oxide is facilitated by the use of low-valent metal oxides and / or mixed-valent metal oxides as curing accelerators, which is conducive to the polymerization reaction between phosphoric acid and cupric oxide / ferric oxide near the cuprous oxide / ferrous oxide interface, and can effectively accelerate the curing speed of the phosphate adhesive under low temperature conditions; at the same time, the low-valent and mixed-valent metal oxides are weaker in alkalinity than alkali metal oxides, and do not directly react with phosphoric acid to release heat, so the initial reaction temperature is low, which solves the problem of too fast curing caused by high initial reaction temperature.
[0009] In the above technical solution, the low-valent metal oxide exists stably at normal temperature and pressure.
[0010] In the above technical solution, the low-valent metal oxide is selected from TiO, Cu 2 O, VO, V 2 O 3 , VO 2 、MnO、NiO、Ti 2 O 3 One or more of the .
[0011] Optionally, the low-valent metal oxide is MnO.
[0012] In the above technical solution, the mixed valence metal oxide is selected from Fe 3 O 4 , Pb 3 O 4 One or more of the .
[0013] Optionally, the mixed valence metal oxide is Fe 3 O 4 .
[0014] In the above technical solution, the mass of the curing accelerator is 0-20% of the mass of the copper oxide / iron oxide, and the amount of the curing accelerator is not 0.
[0015] Optionally, the mass of the curing accelerator is 1%-10% of the mass of the copper oxide / iron oxide.
[0016] If the amount of curing agent accelerator is too high, the adhesive will react too fast and be difficult to control. In addition, too high a curing accelerator addition will affect the cross-linking polymerization of the main structure copper oxide phosphate, further affecting the bonding strength. The more curing accelerator is added, the faster the reaction speed. Generally, an amount of about 5% of the mass of copper oxide can have a significant promoting effect. An amount exceeding 20% of the mass of copper oxide will cause the reaction speed to be too fast, release a large amount of heat in a short time, and make the adhesive lose its application period.
[0017] In the above technical solution, when the low-valent metal oxide and the mixed-valent metal oxide are used in combination, the two can be mixed in any mass ratio.
[0018] In the above technical solution, the ratio of the added amount of phosphate-based glue to copper oxide / iron oxide is 1 mL: (0.1-10) g.
[0019] Optionally, the ratio of phosphate-based glue to copper oxide is 1 mL:3 g.
[0020] In the above technical solution, the density of the phosphate-based adhesive is (1.7-1.9) g / cm 3 , the particle size of copper oxide / iron oxide is less than 100μm.
[0021] The addition ratio of the phosphate-based adhesive to the copper oxide in the phosphate adhesive provided by the present invention can be adjusted within a range as required.
[0022] In the above technical solution, the phosphate-based glue can be any phosphate-based glue, generally selected from one or more of aluminum phosphate-based glue, chromium phosphate-based glue, aluminum chromium phosphate-based glue, magnesium phosphate-based glue, and zirconium phosphate-based glue.
[0023] The second object of the present invention is to provide a method for preparing a phosphate adhesive, comprising: mixing a phosphate-based adhesive and copper oxide and then adding a curing accelerator to obtain the phosphate adhesive.
[0024] The third object of the present invention is to provide another method for preparing a phosphate adhesive, comprising: mixing a curing accelerator and copper oxide / iron oxide and then adding a phosphate-based glue to obtain a phosphate adhesive.
[0025] The fourth object of the present invention is to provide another method for preparing a phosphate adhesive, comprising: mixing a curing accelerator, copper oxide / iron oxide, and a phosphate-based adhesive simultaneously to obtain a phosphate adhesive.
[0026] The curing accelerator can be added after the phosphate-based adhesive and copper oxide / iron oxide are mixed, or the curing accelerator and copper oxide / iron oxide can be pre-mixed and mixed with the phosphate-based adhesive as a whole, or the phosphate-based adhesive, copper oxide / iron oxide and curing accelerator can be mixed at the same time.
[0027] The present invention adopts low-valent metal oxides and / or mixed-valent metal oxides as curing accelerators to prepare phosphate adhesives. Compared with the prior art, under the same gluing time conditions, the curing speed of the adhesive after gluing is faster. This feature is particularly obvious when the ambient temperature is low, such as 10°C, and the amount of curing accelerator used is less.
[0028] After adopting the above technical scheme, the present invention has the following beneficial effects compared with the prior art.
[0029] The technical solution provided by the present invention adopts low-valent metal oxides and / or mixed-valent metal oxides as curing accelerators to prepare phosphate adhesives. Compared with the adhesives prepared by using alkali metals as curing accelerators in the prior art, under the condition of the same application period, the adhesive provided by the present invention has higher curing strength and less curing accelerator, which solves the contradiction between sufficient gluing time and higher curing strength in the prior art. In addition, the preparation method is simple, efficient, and easy to realize industrial production, making the application of the adhesive more extensive and flexible. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments will be clearly and completely described below in combination with the embodiments of the present invention. The following embodiments are used to illustrate the present invention but are not used to limit the scope of the present invention.
[0031] Example 1
[0032] (1) Prepare raw materials: density 1.80g / cm 3 The phosphate (Al / P=1:23) based glue, the particle size distribution of copper oxide is 55um (D50 value), and the curing accelerator is commercially available analytically pure low-valent metal oxide Ti 2 O 3 .
[0033] (2) Determine the test method: To test the performance of the adhesive, tensile test specimens are prepared in accordance with the national standard GB7124-86, and the shear tensile strength is tested using an electronic tensile testing machine.
[0034] (3) Glue adjustment and performance testing steps:
[0035] At room temperature, mix 25mL of phosphate-based adhesive and 75g of copper oxide in a 250mL beaker (time 20s). At this time, the mixing ratio of phosphate-based adhesive and copper oxide is 1mL:3g. Then add the curing accelerator, stir for 20s until all components are mixed evenly, and then start timing as the starting time of the adhesive's applicable period. At the same time as the timing starts, use the adhesive to paste two tensile test pieces. The two pasted tensile pieces are placed in a constant temperature box at 25℃ and 10℃ for constant temperature assessment. After 12h, the shear tensile strength is tested. Continue to stir the remaining adhesive until it is in a state where it is difficult to flow, stop timing, and record this time as the adhesive's applicable period.
[0036] (4) The dosage of the curing accelerator and the performance test results of the phosphate-copper oxide adhesive are shown in Table 1.
[0037] Example 2
[0038] The curing accelerator is a commercially available analytically pure mixed valence metal oxide Fe 3 O 4 The other raw materials, adhesive preparation and performance test steps are the same as those in Example 1. The dosage of the curing accelerator and the performance test results of the phosphate-copper oxide adhesive are shown in Table 1.
[0039] Example 3
[0040] The curing accelerator is commercially available analytically pure low-valent metal oxide MnO and mixed-valent metal oxide Fe. 3 O 4 A mixture of MnO and Fe 3 O 4 The mixing mass ratio is 1:2. Other raw materials, adhesive preparation and performance test steps are the same as those in Example 1. The dosage of the curing accelerator and the performance test results of the phosphate-copper oxide adhesive are shown in Table 1.
[0041] Example 4
[0042] In addition to MnO and Fe in the curing accelerator 3 O 4 Except that the mixing mass ratio is 1:1, the other aspects are exactly the same as those in Example 3. The dosage of the curing accelerator and the performance test results of the phosphate-copper oxide adhesive are shown in Table 1.
[0043] Example 5
[0044] In addition to MnO and Fe in the curing accelerator 3 O 4 Except that the mixing mass ratio is 2:1, the other aspects are exactly the same as those in Example 3. The dosage of the curing accelerator and the performance test results of the phosphate-copper oxide adhesive are shown in Table 1.
[0045] Example 6
[0046] (1) Prepare raw materials: density 1.80g / cm 3 The phosphate (Al / P=1:23) based glue, the particle size distribution of iron oxide is 80um (D50 value), and the curing accelerator is commercially available analytically pure low-valent metal oxide Ti 2 O 3 .
[0047] (2) Determine the test method: To test the performance of the adhesive, tensile test specimens are prepared in accordance with the national standard GB7124-86, and the shear tensile strength is tested using an electronic tensile testing machine.
[0048] (3) Glue adjustment and performance testing steps:
[0049] At room temperature, mix 25mL of phosphate-based adhesive and 75g of iron oxide in a 250mL beaker (time 20s). At this time, the mixing ratio of phosphate-based adhesive and iron oxide is 1mL:3g. Then add curing accelerator, stir for 20s until all components are mixed evenly, and then start timing as the starting time of the adhesive's applicable period. At the same time as the timing starts, use the adhesive to paste two tensile test pieces. The two pasted tensile pieces are placed in a constant temperature box at 25℃ and 10℃ for constant temperature assessment. After 12h, the shear tensile strength is tested. Continue to stir the remaining adhesive until it is in a state where it is difficult to flow, stop timing, and record this time as the adhesive's applicable period.
[0050] (4) The dosage of curing accelerator and the performance test results of phosphate-iron oxide adhesive are shown in Table 2.
[0051] Example 7
[0052] The curing accelerator is a commercially available analytically pure mixed valence metal oxide Fe 3 O 4 The other raw materials, adhesive preparation and performance test steps are the same as those in Example 6. The dosage of the curing accelerator and the performance test results of the phosphate-iron oxide adhesive are shown in Table 2.
[0053] Example 8
[0054] The curing accelerator is commercially available analytically pure low-valent metal oxide MnO and mixed-valent metal oxide Fe. 3 O 4 A mixture of MnO and Fe3 O 4 The mixing mass ratio is 1:2. Other raw materials, adhesive preparation and performance test steps are the same as those in Example 6. The dosage of the curing accelerator and the performance test results of the phosphate-iron oxide adhesive are shown in Table 2.
[0055] Example 4
[0056] In addition to MnO and Fe in the curing accelerator 3 O 4 Except that the mixing mass ratio is 1:1, the other aspects are exactly the same as those in Example 8. The dosage of the curing accelerator and the performance test results of the phosphate-iron oxide adhesive are shown in Table 2.
[0057] Example 5
[0058] In addition to MnO and Fe in the curing accelerator 3 O 4 Except that the mixing mass ratio is 2:1, the other aspects are exactly the same as those in Example 8. The dosage of the curing accelerator and the performance test results of the phosphate-iron oxide adhesive are shown in Table 2.
[0059] Comparative Example 1
[0060] The curing accelerator is magnesium oxide, and the other raw materials, adhesive preparation and performance test steps are the same as those in Example 1. The dosage of the curing accelerator and the performance test results of the phosphate-copper oxide adhesive are shown in Table 1.
[0061] Table 1:
[0062]
[0063] Comparative Example 2
[0064] The curing accelerator is magnesium oxide. Other raw materials, adhesive preparation and performance test steps are the same as those in Example 6. The dosage of the curing accelerator and the performance test results of the phosphate-iron oxide adhesive are shown in Table 2.
[0065] Table 2:
[0066]
[0067] Conclusion: When preparing phosphate-copper oxide adhesives in Examples 1-5 and Comparative Example 1, Example 1 uses low-valent metal oxide Ti 2 O 3 As a curing accelerator, Example 2 uses a mixed valence metal oxide Fe 3 O 4 As a curing accelerator, Examples 3-5 use mixed valence metal oxides Fe in different mass ratios. 3 O 4and a mixture of low-valent metal oxide MnO as a curing accelerator, compared with the phosphate-copper oxide adhesive prepared in Comparative Example 1 using metal oxide magnesium oxide as a curing accelerator, under the condition of the same adhesive application period, its tensile strength has been significantly improved, and the amount of curing accelerator used has been significantly reduced; wherein, compared with Example 1, Example 2 has a higher tensile strength under the condition of a lower ambient temperature of 10°C, indicating that when preparing the phosphate-copper oxide adhesive, under the condition of a lower ambient temperature of 10°C, Fe 3 O 4 As a curing accelerator, compared with Ti 2 O 3 As a curing accelerator, the tensile strength is higher when the adhesive has the same pot life.
[0068] When preparing phosphate-iron oxide adhesives in Examples 6-10 and Comparative Example 2, Example 6 uses low-valent metal oxide Ti 2 O 3 As a curing accelerator, Example 7 uses a mixed valence metal oxide Fe 3 O 4 As a curing accelerator, Examples 8-10 use mixed valence metal oxides Fe in different mass ratios. 3 O 4 and a mixture of low-valent metal oxide MnO as a curing accelerator, compared with the phosphate-copper oxide adhesive prepared in Comparative Example 2 using metal oxide magnesium oxide as a curing accelerator, under the condition of the same adhesive application period, its tensile strength has been significantly improved, and the amount of curing accelerator used has been significantly reduced; among them, compared with Example 6, Example 7 has a higher tensile strength under the condition of a lower ambient temperature of 10°C, indicating that when preparing the phosphate-iron oxide adhesive, under the condition of a lower ambient temperature of 10°C, Fe 3 O 4 As a curing accelerator, compared with Ti 2 O 3 As a curing accelerator, the tensile strength is higher when the adhesive has the same pot life.
[0069] It can be seen that the present invention provides a technical solution for preparing a phosphate adhesive using low-valent metal oxides and / or mixed-valent metal oxides as a curing accelerator. Under the same gluing time conditions, the adhesive after gluing cures faster and obtains higher curing strength, while the amount of curing accelerator used is less.
[0070] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with the present invention can make some changes or modify the technical contents suggested above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the solution of the present invention.
Claims
1. A phosphate adhesive, characterized in that: The raw materials of the phosphate adhesive include phosphate-based adhesive, copper oxide / iron oxide, and a curing accelerator, and the curing accelerator is a low-valent metal oxide and / or a mixed-valent metal oxide.
2. A phosphate adhesive according to claim 1, characterized in that: The low-valent metal oxide exists stably at normal temperature and pressure.
3. A phosphate adhesive according to claim 1 or 2, characterized in that: The low-valent metal oxide is selected from one or more of TiO, Cu2O, VO, V2O3, VO2, MnO, NiO, and Ti2O3; Preferably, the low-valent metal oxide is MnO.
4. A phosphate adhesive according to claim 1, characterized in that: The mixed valence metal oxide is selected from one or more of Fe3O4 and Pb3O4; Preferably, the mixed valence metal oxide is Fe3O4.
5. A phosphate adhesive according to any one of claims 1 to 4, characterized in that: The mass of the curing accelerator is 0-20% of the mass of the copper oxide / iron oxide, and the mass of the curing accelerator is not 0; Preferably, the mass of the curing accelerator is 1%-10% of the mass of the copper oxide / iron oxide.
6. A phosphate adhesive according to any one of claims 1 to 4, characterized in that: The ratio of the amount of phosphate-based glue added to copper oxide / iron oxide is 1 mL: (0.1-10) g; Preferably, the ratio of the added amount of phosphate-based glue to copper oxide or iron oxide is 1 mL:3 g.
7. A phosphate adhesive according to claim 5, characterized in that: The density of phosphate-based glue is (1.7-1.9) g / cm 3 , the particle size of copper oxide / iron oxide is less than 100μm.
8. A phosphate adhesive according to any one of claims 1 to 4, characterized in that: The phosphate-based glue is selected from one or more of aluminum phosphate-based glue, chromium phosphate-based glue, aluminum chromium phosphate-based glue, magnesium phosphate-based glue, and zirconium phosphate-based glue.
9. A method for preparing a phosphate adhesive according to any one of claims 1 to 8, characterized in that: include: After mixing phosphate-based glue and copper oxide / iron oxide, a curing accelerator is added to obtain a phosphate adhesive; or after mixing the curing accelerator and copper oxide / iron oxide, the phosphate-based glue is mixed to obtain a phosphate adhesive; or after mixing phosphate-based glue, copper oxide / iron oxide and a curing accelerator together, a phosphate adhesive is obtained.
10. Use of low-valent metal oxides and / or mixed-valent metal oxides as curing accelerators in the preparation of phosphate-copper oxide adhesives or phosphate-iron oxide adhesives.
Citation Information
Patent Citations
High temperature resistant inorganic adhesive
CN101307212A
Phosphates adhesive and preparation method thereof
CN101358111A